Identification of novel antimicrobial peptides from rice planthopper, Nilaparvata lugens. (October 2019) - Zhou, Xiang; Peng, Lu-Yao; Wang, Zhe-Chao; Wang, Wei; Zhu, Zhen; Huang, Xiao-Hui; Chen, Li-Bo; Song, Qi-Sheng; Bao, Yan-Yuan
Abstract: In this study, two novel antibacterial peptide genes, termed lugensin A and B were identified and characterized from a rice sap-sucking hemipteran insect pest, the brown planthopper, Nilaparvata lugens . Lugensin gene expression was significantly induced by Gram-negative and Gram-positive bacterial stains under the regulation of a signal receptor, the long peptidoglycan recognition protein (PGRP-LC) in the IMD pathway. Knockdown of PGRP-LC by RNAi eliminated bacterium induced Lugensin gene expression. Lugensins had the apparent antibacterial activities against Escherichia coli K12, Bacillus subtilis and the rice bacterial brown stripe pathogen Acidovorax avenae subsp. avenae ( Aaa ) strain RS-1. Lugensins inhibited bacterial proliferation by disrupting the integrity of the bacterial membranes. Scanning electron microscopy revealed abnormal membrane morphology of the recombinant Lugensin-treated bacteria. Lugensins induced complete cell disruption of E. coli K12 and B. subtilis strains while formed the holes on the cell surface of Aaa RS-1 strain. Immunofluorescence showed that Lugensins localized in the cell membrane of E. coli K12 while accumulated in the cytosol of B. subtilis . Differently, Lugensins remained in both the cell membrane and the cytosol of Aaa RS-1 strain, suggesting different action modes of Lugensins to different microbes. This is the first report of the novel antibacterial peptides found in the rice sap-sucking hemipteran insect species. Graphical abstract: Image 1 Highlights: Two novel antibacterial peptides, Lugensins were found in a phloem-sucking insect, N. lugens . Gram-negative and -positive bacteria activated Lugensin gene expression. PGRP-LC, a signal receptor in the Imd pathway, regulated Lugensin gene expression. Lugensins had antibacterial activities against Gram-negative and -positive bacteria strains. Lugensins displayed the different action models on the membranes of the bacteria strains.